Novitates neocaledonicae III: A new species of Citronella (Cardiopteridaceae) endemic to New Caledonia - Munzinger, Jerome; Levionnois, Sebastien (Phytotaxa, 2016)
A new species of Cardiopteridaceae, Citronella hirsuta, endemic to the east-central part of New Caledonia’s main island, Grande Terre, distinguished on the basis of morphological evidence, is described and illustrated. This new species is distinguished by its densely hirsute leaves, while the two others species of Citronella occurring in New Caledonia have glabrous leaves. Citronella hirsuta is restricted to ultramafic substrate, and only known from areas that are situated within mining concessions. A preliminarily IUCN conservation status of Endangered (EN) is proposed.